Pengaruh Terapi Aktivitas Kelompok Sosialisasi Terhadap Kemampuan Komunikasi Verbal Klien Menarik Diri Di Rsjd Surakarta - Dwi Wahyu Pangestu; Arif Widodo (Jurnal Berita Ilmu Keperawatan, 2017)
Results of preliminary studies that have been conducted by researchers at the Regional Mental Hospital (RSJD) Surakarta, which states that information obtained in previous Surakarta RSJD has taken various therapeutic modalities, one group activity therapy conducted over a period of one month or four times a week once exactly on Thursday. data showed that the incidence of schizophrenia with the number 17 763. 2,105 hebephrenic Schizophrenia, paranoid 37, not defined 94, 243 catatonic, residual 7,767, simplex 28, the other 7489. While the incidence of schizophrenia in 2011 with the number 18 022. 1,909 hebephrenic, not defined Schizophrenia, paranoid 407, not defined 110,224 catatonic, residual 8158, simplex 24, the other 7,190. Objective: To determine the effect of therapy group socialization activity not defined y against the client’s verbal communication skills in RSJD Surakarta withdrew after a given treatment group. Methods research: The design of this study is to use the design pra-experiment Posttest Only Design. The population in this study totaling 211 patients based on medical records of people with impaired verbal communication on the client withdrew. Sample set of 30 respondents to the purposive sampling technique. The analytical tool used by descriptive analysis. Conclusions